How does understanding scripture prepare for evangelization? - Tan, Paulus Satyo Istandar (Educenter : Jurnal Ilmiah Pendidikan, 2024)
Preachers as servants who are given the task of conveying the word of God must have a strong understanding of the verses to be conveyed, so that there will be no mistakes or multiple interpretations in their preaching. The purpose of this study is to provide a deeper understanding of the Word of God so that we can communicate it with power and relevance in our daily lives. This research utilizes a qualitative method. This method involves analyzing the theology contained in the biblical text, including the study of theological concepts such as grace, justice, salvation, and others. Data collection techniques were conducted through in-depth analytical analysis of the biblical text itself. The study concluded that the call to serve others, build inclusive communities, and trust in God's active work in bringing salvation to His people are at the core of Christianity. So it is important to live the Christian faith with dedication, loyalty, and love for God and others, thus strengthening the vertical relationship with God and horizontal with fellow humans in realizing grace and justice in the world.